Malignant NK/T-Cell Lymphoma Associated with Simian Epstein-Barr Virus Infection in a Japanese Macaque (Macaca fuscata) - FUKUOKA, Ayumi; DOI, Kunio; MIWA, Norikatsu; HASHIMOTO, Chihiro; NAKAYAMA, Hiroyuki; ISOWA, Koichi; ISHIDA, Takafumi; KATO, Akino; GOTO, Shunji; SUZUKI, Juri; TAKAO, Satomi (EXPERIMENTAL ANIMALS, 2005)
A case of spontaneous malignant lymphoma in a Japanese macaque (Macaca fuscata) was pathologically, etiologically and virologically studied. Nasal cavity was involved in the neoplastic lesions in addition to lymphoid and visceral tissues. Histopathological analyses revealed the presence of neoplastic cells classified into histiocytic Hodgkin-like cells and Reed-Sternberg-like cells. Histiocytic Hodgkin-like cells were CD16+ and CD20+, and the CD16+ cells were also positive for simian Epstein-Barr virus (sEBV)-encoded early RNA transcripts. RS-like cells were negative for CD3, CD16 and CD20. Antibodies to early antigen of sEBV were detected, while antibodies to simian T-cell leukemia virus-1 were negative. The case may correspond to EBV-associated nasal type NK/T-cell lymphoma in humans rather than Hodgkin lymphoma.